2001
DOI: 10.1093/molehr/7.7.625
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of SOB3, a human gene coding for a sperm protein homologous to an antimicrobial protein and potentially involved in zona pellucida binding

Abstract: We have previously characterized an 18-19 kDa cationic protein, SOB3, that was detected in the epididymis and localized within the acrosome and on the neck region of human spermatozoa. We suggested that it is involved in secondary sperm binding to the zona pellucida. The present study describes its purification to homogeneity by preparative electrophoresis and non-equilibrium pH gradient electrophoresis. Degenerate primers deduced from microsequencing were used to amplify a specific fragment from human epididy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
3
21
0
1
Order By: Relevance
“…This strict control of generation of LL-37 is probably important because of the cytotoxic effects of this peptide (43). The hCAP-18 in seminal plasma is derived from epithelial cells in epididymis (22,23), whereas gastricsin is derived from the prostatic gland and seminal vesicles (44). Thus, hCAP-18 and gastricsin only co-localize following ejaculation.…”
Section: Table II Bacteriolytic Effect Of Ll-37 and All-38 On Growingmentioning
confidence: 99%
See 2 more Smart Citations
“…This strict control of generation of LL-37 is probably important because of the cytotoxic effects of this peptide (43). The hCAP-18 in seminal plasma is derived from epithelial cells in epididymis (22,23), whereas gastricsin is derived from the prostatic gland and seminal vesicles (44). Thus, hCAP-18 and gastricsin only co-localize following ejaculation.…”
Section: Table II Bacteriolytic Effect Of Ll-37 and All-38 On Growingmentioning
confidence: 99%
“…in various squamous epithelia (16), in the lungs (17,18), in sweat glands (19), in salivary glands (20), and in keratinocytes during inflammatory disorders (21)). The strongest epithelial expression of hCAP-18 is found in the epididymis with a subsequent high concentration in seminal plasma (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…La s6quence nucl6otidique codant pour une prot6ine impliqu6e dans la liaison h la ZP (P34H), identifie celle-ci comme appartenant h la famille << d6shydrog6nase/r6ductase ~>. Une autre prot6ine impliqu6e dans la liaison ~t la ZP, SOB3 [24], a une s6quence identique ~ celle d'une prot6ine cationique anti-microbienne originaire de l'6pididyme humain : hCAP-18 [37].…”
Section: Des S P E R M a T O Z O I D E Sunclassified
“…Recent studies have shown that EPECs of rat, mice and human synthesize molecules having antimicrobial activities. Some of them are Bin-1β [9], Eppin [8] , SPAG-11 [2], HE2-α [10], β-defensins [2,11], SOB3 [12], EP2/HE2 [4], hCAP-18 [13], and cystatin-11 [14] etc. Despite the progress made in other species, the repertoire of host defense molecules also known as antimicrobial peptides (AMPs) having microbicidal activities have not been investigated previously in the epididymis of rabbit, Oryctologus cuniculus.…”
Section: Introductionmentioning
confidence: 99%